DNA Methylation Biphasically Regulates 3T3-L1 Preadipocyte Differentiation - Yang, Xiaosong (Mol Endocrinol, 2016)
Better understanding the mechanisms underlying adipogenesis may provide novel therapeutic targets in the treatment of obesity. Most studies investigating the mechanisms underlying adipogenesis focus on highly regulated transcriptional pathways; little is known about the epigenetic mechanisms in this process. Here, we determined the role of DNA methylation in regulating 3T3-L1 adipogenesis in early and late stage of differentiation. We found that inhibiting DNA methylation pharmacologically by 5-aza-2′-deoxycytidine (5-aza-dC) at early stage of 3T3-L1 differentiation markedly suppressed adipogenesis. This inhibition of adipogenesis by 5-aza-dC was associated with up-regulation of Wnt10a, an antiadipogenic factor, and down-regulation of Wnt10a promoter methylation. In contrast, inhibiting DNA methylation by 5-aza-dC at late stage of differentiation enhanced the lipogenic program. The differential effects of 5-aza-dC on adipogenesis were confirmed by gain or loss of function of DNA methyltransferase 1 using genetic approaches. We further explored the molecular mechanism underlying the enhanced lipogenesis by inhibition of DNA methylation at late stage of differentiation. The Srebp1c promoter is enriched with CpG sites. Chromatin immunoprecipitation assays showed that DNA methyltransferase 1 bound to the methylation region at the Srebp1c promoter. Pyrosequencing analysis revealed that the DNA methylation at the key cis-elements of the Srebp1c promoter was down-regulated in adipogenesis. Further, luciferase reporter assays showed that the Srebp1c promoter activity was dramatically up-regulated by the unmethylated promoter compared with the fully methylated promoter. Thus DNA methylation appears to exert a biphasic regulatory role in adipogenesis, promoting differentiation at early stage while inhibiting lipogenesis at late stage of 3T3-L1 preadipocyte differentiation.